Pharmacoeconomic Education for Pharmacy Students in Bosnia and Herzegovina - Catić, Tarik (AVICENA, d.o.o., Sarajevo, 2013)
Pharmacoeconomic (PE) is becoming more important in pharmaceutical reimbursement decision and drug evaluation. To ensure its appropriate application, conduction and assessment of studies it is important to have well trained and educated professionals. Pharmaceutical faculties all over the world have established PE in under- and post-graduate curricula’s. In this pilot research we examine situation in B&H. In Bosnia-Herzegovina, education in this field is poor and only one faculty for pharmacy has introduced PE as subject in its program. Objective of this study is to explore understanding of PE and its concept and analysis and to evaluated adopted knowledge among graduate (fifth year/tenth semester) pharmacy students who have listened subject “pharmacoeconomics” in previous semester. A self-administered questionnaire was developed consisted of 12 questions and survey was conducted among students. Results are analyzed in MS Excel and we used descriptive statistics. Even graduate students have lessons from PE they understand its scope and definition, but do not feel capable for conducting PE studies, but show interest in additional education and getting competencies in this field finding it applicable in their future professional engagements.